PENERAPAN MODEL PROJECT BASED LEARNING TERINTEGRASI CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATERI JARING-JARING SISWA KELAS IV SEKOLAH DASAR - Siti Zahrotul Ulumul Fitria; Vicky Dwi Wicaksono; Ika Nur Jannah; Selviari; Satrio Budiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The low learning outcomes in the cognitive aspects of class IV A students using mathematics subject matter is the background to the problem of this research. The aim of conducting the research is to describe the implementation of student activities and learning outcomes on students' cognitive aspects in implementing the Project Based Learning model integrated with Culturally Responsive Teaching with network materials. Kemmis and Taggart's model in the pre-cycle and 2 learning cycles including planning, implementation, observation and reflection is used in this classroom action research method. The research subjects were 29 students in class IV A of SDN Dukuh Kupang III/490 Surabaya. Tests and observations are used to obtain research data. The data obtained was analyzed using techniques, namely descriptive qualitative. The results of research on the implementation of student activities in cycle I included a percentage of 57.5%, while in cycle II the percentage increased by 32.5% to 90%. Learning outcomes in the cognitive aspect of students also show a percentage increase. The first cycle component showed 45% (13) complete learning and 55% (16) incomplete learning and an average class score of 65.17. Meanwhile, the second cycle component showed 83% (24) learning completeness and 17% (5) incomplete learning and an average class score of 85.86. From the research data obtained, it can be said that the application of the Project Based Learning model integrated with Culturally Responsive Teaching has been proven to improve the learning outcomes of class IV elementary school students.